Faktor-Faktor yang Mempengaruhi Opini Audit Going Concern Pada Perusahaan Agrikultur yang Terdaftar di BEI - Dini Atikah; Dewi Sartika (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2021)
Abstract This study aims to examine the effect of leverage and audit quality on going concern audit opinions. Things that happen in a company that goes bankrupt and cannot maintain the company's viability. Then the going concern audit opinion is defined as the auditor's statement for the company's ability to survive the company. Leverage as the company's ability to fulfill all obligations. Audit quality is the auditor's ability to find material misstatements and manipulation practices in the financial statements to produce fair financial statements and can be used as a basis for decision making. The research design uses quantitative methods by collecting financial statement data through the website www.idx.co.id. The population in this study were agricultural companies in the oil palm plantation sector which were listed on the Indonesia Stock Exchange for 5 years (2016-2020). Sample selection using purposive sampling method, and obtained as many as 14 companies. Data collection techniques using library research and documentation. The analytical method used in this study is logistic regression analysis and uses data processing tools with the SPSS application program. The results of this study partially show that leverage has a positive effect on going-concern audit opinion, while audit quality has no significant effect but has a positive effect on going-concern audit opinion. Simultaneously, leverage and audit quality have an effect on going-concern audit opinion. Keyword: Going Concern Audit Opinions, Leverage, Audit Quality